Designing Digital Modules in Project-Based Learning-Based Printing Graphic Design Subjects at SMK N 1 Koto Baru Dharmasraya - Huda, Asrul; Febrianti, Widia; Firdaus; Hendriyani, Yeka; Bayu Ramadhani Fajri; Murni Sukmawati (International Journal of Interactive Mobile Technologies (iJIM), 2024)
Learning in the 21st century is directed towards activities that train students’ skills, emphasizing the learning process. This can be achieved by optimizing the use of technology as an educational tool, one of which is using digital learning media in the form of modules, utilizing a project-based learning model. In the development of project-based learning digital modules, the multimedia development life cycle (MDLC) development model is employed. In the process of creating this digital module application, Unity software is used as the main software to manage content layout and animation. Adobe Illustrator is used for creating UI and required assets, while Visual Studio code is utilized for coding the application. Overall, the digital module in the subject of graphic design printing has successfully passed the validity test with very positive results. Based on the practicality analysis of the digital module in the graphic design printing subject, it can be concluded that the module is highly practical for both teachers and students.